Inflation and the Trade Credit Period - Ben-Horim, Moshe; Levy, Haim (Management Science, 1982)
Management of accounts receivable and trade credit policy should often be adjusted to reflect changing interest rates due to changing inflation. Firms can respond to inflation by either increasing the discount for cash payments or by shortening the credit period. This paper investigates the policy of shortening the credit period in response to changing inflation rates. We first assume that inflation is fully anticipated, and later we extend the analysis to incorporate inflation risk.